THE TRANSFORMATIVE MIND: EXPANDING VYGOTSKY’S APPROACH TO DEVELOPMENT AND EDUCATION - Bento Selau (Psicologia em Estudo, 2020)
Review (Stetsenko, A. (2017). The Transformative Mind: Expanding Vygotsky’s Approach to Development and Education. New York, NY: Cambridge University Press. 331 p.)